Protective effects of some Nigerian indigenous antimalarial plants on placental malaria related pathological damages and pregnancy outcomes in murine model. Issue 1 (1st January 2020) - Babalola, Ayodele S.; Idowu, Olufunmilayo A.; Ademolu, Kehinde O.; Olukunle, J.; Rahman Samson, A.
ABSTRACT: Research evidence attempting to evaluate the safety and efficacy of herbs use by pregnant women against malaria in Africa are seriously lacking. This study seeks to determine efficacy of 3 antimalarial plants commonly used by pregnant women in Nigeria on placental malaria and pregnancy outcome in murine model. The experiment was carried out in 110 experimental pregnant mice randomly distributed into 22 groups and treated with extracts of M. lucida, E. chlorantha, and C. citatrus at a graded dose of 100, 200, and 300 mg/kg. The positive control was treated with fansidar at 10 mg/kg while the negative control was not treated. Extract of M. lucida and E. chlorantha recorded over 70% chemosuppression at the highest dose of 300 mg/kg body weight. While extract of E. chlorantha induced abortion in pregnant mice at all concentrations, extract of M. lucida and C. citatrus caused miscarriage at the highest dosage. Malaria related pathological damages were more pronounced in placenta of mice treated with C. citatrus, it was reduced to the barest minimum in mice treated with extracts of M. lucida . The use of herbs was significantly associated with poor pregnancy outcomes (pups weight, pups mortality, and litter size) in this study.